Holocene vegetation dynamics and climate changes in the Torneträsk area, northern Sweden - Barnekow, Lena (Department of Quaternary Geology, Lund University, 1999)
The aim of this study was to reconstruct the Holocene vegetation history and the climate changes in a subarctic area. The results are based on pollen and macrofossil records from six lakes in the Torneträsk area. The lakes are situated at altitudes between 370 and 999 m a.s.l., along a transect from the boreal pine-birch forest to the alpine tundra with heath vegetation. The chronology in each lake is based on radiocarbon dated terrestrial plant macrofossils and combined with varve chronology in one of the lakes. Ages from radiocarbon dated plant macrofossils were compared with ages from radiocarbon dated bulk sediment samples in two of the lakes. The results show that radiocarbon dated bulk sediment samples give older ages compared to the macrofossil samples. The age differences varied between 550 and 2200 years in samples from a lake with calcareous rich sediment and between 250 and 800 years in samples from lake sediment with a low carbonate carbon content. Erroneous high ages from bulk sediment samples will not only effect the chronology, but will also lead to incorrect pollen-influx calculations. The results of this study also indicate that the tree-line, which consists of mountain birch ( Betula pubescens ssp. tortuosa ), was situated c. 300-400 m above the present tree-line during the early and the mid-Holocene. When land up-lift has been taken into account this higher tree-line corresponds to a summer temperature of 1.5-2°C higher than today. The climate was warm and moist during the early Holocene and warm and dry during the mid-Holocene. A pine-birch forest expanded first in the eastern part of the Torneträsk area at c. 8300 cal BP and about 700 years later to the western part at low altitudes. Optimal conditions for pine ( Pinus sylvestris ) occurred between 6300 and 4500 cal BP when the pine-birch forest reached its highest altitude at least 560 m a.s.l., i.e. 110 m above the present pine limit. During this time the pine limit reached 175 m above the present. Dry conditions during this interval are ...